CONDITIONS AND DISEASES IN THE “PORT UNHEALTHY”: MEDICAL KNOWLEDGE CONSTRUCTION HEALTH AND SOCIAL REPRESENTATIONS ABOUT DEATH IN ARICA (1880-1930) - Chávez Zúñiga, Pablo; Soto Lara, José (Revista de Historia Social y de las Mentalidades, 2015)
The purpose of this work is to explain the sanitary context of Arica city. The epidemic outbreaks are common during the period, constructed the social representations of the city as an “unsafe port”. This happened due the present of at least the following diseases: bubonic plague, malarial fevers and other contagious diseases. The paper examines a scenario with poor sanitary conditions, as a result of weak infrastructure, such as the sewagesystems. In that situation several elements came together, highlighting the development of the “social and sanitary issue” that was expressed in a high mortality because government institutions, such hospitals, were considered charities.